Children in Custody Disputes Matching Legal Proceedings to Problems - Kaldal, Anna; Hellner, Agnes; Mattsson, Titti (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book explores how legal proceedings in and out-of-court can be matched to the complex problems underlying disputes concerning child custody, residence and contact between parents. It focusses in particular on Nordic experiences of in and out-of-court mechanisms as means of resolving custody disputes. The contributors are internationally renowned and experienced researchers from the legal, psychological, and sociological fields who provide empirical as well as legal perspectives. They examine central legal, ethical and knowledge-based dilemmas in custody dispute proceedings. The findings speak to an international audience and suggest ways how to best realize the interests of the child. It transcends disciplinary, institutional, and jurisdictional boundaries in search of new knowledge. Anna Kaldal is a professor of procedural law and head of subject at the Faculty of Law, Stockholm university, Sweden. Her main field of research is evidential law and children inlegal proceedings, especially children in custody cases, criminal cases and child protection cases. She is one of the founders of the Stockholm Centre for the Rights of the Child. Agnes Hellner is a senior lecturer in procedural law at the Faculty of Law, Stockholm University, Sweden. Her research focuses on access to justice, comparative procedural law and constitutional law dimensions of procedural law, such as the relationship between the courts and the legislature. Titti Mattsson is a professor of public law at the Faculty of Law, Lund University, Sweden. Her research focuses on legal, ethical and human rights issues within national social welfare systems, including children's rights. Mattsson is heading the Health Law Research Centre at Lund University.